Analisis Usability Website PT. Perkebunan Nusantara (PTPN IX) Untuk Menunjang Industri Kreatif di Era Global - Fadiana; Kristiyanto, Daniel Yeri (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2024)
Technology is rapidly advancing in society and the workplace. PT Perkebunan Nusantara IX (PTPN IX), which operates in the management and marketing of plantation commodities, has utilized technology to facilitate the presentation of downstream product information through a dynamic website. The PTPN IX website plays a crucial role in presenting the company’s latest information. However, the PTPN IX website has never undergone a usability testing process. Therefore, this study aims to analyze the quality of the website in supporting its role and functions. The results of the observations indicate that several users experience problems when accessing the website. To analyze these issues, heuristic evaluation methods were used to identify usability problems on the website, and the System Usability Scale (SUS) to assess the system’s feasibility. This method involved 3 evaluators and 100 users to evaluate the website based on 10 heuristic aspects, which were mapped into sub-aspects according to their severity levels. The overall evaluation results indicated categories of cosmetic issues and minor usability problems. This study identified 10 problems and provided recommendations for improving the PTPN IX website. The improvement recommendations aim to optimize the website system to better fulfill its role and function as an information provider platform related to local commodity products for all elements of society.